Memaksimalkan Kinerja Karyawan dengan Total Quality Management dan Kepuasan Kerja - Sasmita, I Gusti Bagus Nyoman Surya Candra; Wijaya, Putu Yudy; Sugianingrat, Ida Ayu Putu Widani (UNHI Press, 2025)
This study was conducted to analyze the influence of total quality management (TQM) on employee performance directly and through job satisfaction uses an associative quantitative approach to analyze the causal relationship. This research was conducted at Prama Sanur Beach, Bali, which has a population of 257 people. The sample size determined using the Yamane Formula was 157 people with a proportional sampling technique. Data collection was carried out using interview and questionnaire methods. Instrument testing was carried out using validity and reliability tests. The analysis technique used was SEM-PLS. The results of the study prove that TQM has a positive and insignificant effect on employee performance, TQM has a positive and significant effect on job satisfaction, and job satisfaction has a positive and significant effect on employee performance. Job satisfaction mediates the effect of TQM on employee performance perfectly (full mediation).